The Influence of KIA Book-Based Education on Mothers' Attitudes to Danger Signs of Childbirth at Sangowo Community Health Center, Morotai - Fitriani Karno; Rani Safitri (Jurnal Medika Nusantara, 2025)
The high maternal mortality rate remains a health problem in Indonesia, especially in island areas such as Morotai Island Regency. One contributing factor is the low awareness of mothers regarding danger signs of childbirth. The Maternal and Child Health Book (MCH Book) is an educational medium that can improve mothers' knowledge and attitudes in facing the risks of childbirth. This study aims to determine the effect of MCH Book-based education on mothers' attitudes towards danger signs of childbirth at Sangowo Community Health Center, Morotai Island Regency. The study used a pre-experimental design with a one-group pretest - posttest approach. The study sample consisted of 24 pregnant women in their second and third trimesters who met the inclusion criteria and were willing to participate in education. Data analysis was performed using the Wilcoxon Signed Rank Test to determine differences in attitudes before and after education. The results showed an increase in the median score of mothers' attitudes from 57 in the pretest to 72 in the posttest. The Wilcoxon test showed a significant difference between the pretest and posttest scores (Z = -4.123; p = 0.000). MCH Book-based education had a significant effect on improving mothers' attitudes towards danger signs of childbirth. Systematic, interactive, and family-involved strengthening of education is crucial for improving maternal safety, particularly in island regions with limited access to health facilities.